Analisis Akuntabilitas Pengelolaan Dana Desa - Primasari, Dona; Waspodo, Lego (Jurnal Riset Akuntansi Soedirman, 2025)
This study aims to determine and analyze the influence of community participation and understanding of village institutions on the accountability of village management. The data used in this study are primary data obtained through observation, interviews, and documents. The data analysis method used is qualitative, with the research results presented in the form of descriptive narratives. The population in this study consists of all village officials in the Village Government of X Subdistrict, Banyumas Regency. The sampling technique used in this study was purposive sampling, with a sample size of 45 respondents consisting of village heads, village secretaries, and village treasurers. The testing method used in this study was multiple linear regression analysis. The results of this study indicate that community participation and the understanding of village officials influence the accountability of village fund management.